NURSE KNOWLEDGE ABOUT PATIENT SAFETINESS WITH THE IMPLEMENTATION OF MEDICAL INJECTION (Studies On Opname Unit Dr.Sayidiman Hospital Magetan) - Ahmad Arif Darmawan; Ahmad Arif Wijaya; Yunan Yusuf Habibi (JIWA INTER PLUS, 2011)
Patient safety is a global issue that is most important at this time and there are now reported to the demands of patients on medical errors that happened to him. Cases of improper administration of drugs or excessive medical treatment often occurs in Indonesia, just not exposed to the mass media. Professional nurses have an important role in the implementation of drug administration. This study aims to determine the relationship of nurses' knowledge about the salvation of patients with adherence pelaksnaan injections in the inpatient hospital Dr. Sayidiman Hove.Analytical Methods Cross-sectional study that researchers take measurements or research at a time. Population of 59 nurses with samples taken all inpatient hospital nurses Sayidiman Dr. Hove as many as 59 people. The technique used in this study is the total sampling technique. Data collection using questionnaires. Independent variables of knowledge of nurses about patient safety and compliance implementation dependent variable injection drug delivery. Data processing is done with the editing, coding, scoring, tabulating and using the Pearson correlation test.The results of the 59 respondents knowledge of nurses on patient safety has a correlation coefficient with the compliance of the implementation of injection drug delivery with a significance value of p-value = 0.000> 0.05 where the value of r = 0.580, which means there salvation neighbor relations nurses' knowledge of patients with medication adherence injection execution.The conclusion of this study, most of the knowledge of nurses about patient safety with the implementation of medication adherence injection drug administration is approaching the maximum value. To further enhance the knowledge of nurses on patient safety compliance so as drug delivery injection execution carried out in accordance with procedures.